2021
DOI: 10.2991/ahsr.k.210115.110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compression Bandage on the Healing of Diabetic Foot Ulcers: A Scooping Review

Abstract: Compression Therapy is a non-invasive application in the treatment of leg wounds. Bandage that is not done will cause lower leg edema when the swollen exudate is retained on the surface of the wound which will result in maceration of the skin around the wound, in cases of venous blood vessels there is a high risk of plasma leakage and venous thrombosis and cross infection of the factor. external so that healing can prolong the healing of diabetic foot wounds. Pressure dressings are implemented to improve the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Compression therapy strategies to manage lower limb oedema where a diabetic foot ulcer is present, mapped against the review objectives, can be viewed in Table 3. This scoping review found eleven pieces of information across all of the literature, suggesting that compression bandaging was an effective way to reduce and manage oedema (as detailed in Table 1 and 2), which additionally could have beneficial effects on the healing of DFU [16, 19–26, 29, 40]. One scoping review [16] was found which explored the effect of compression bandaging on the healing of DFU.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Compression therapy strategies to manage lower limb oedema where a diabetic foot ulcer is present, mapped against the review objectives, can be viewed in Table 3. This scoping review found eleven pieces of information across all of the literature, suggesting that compression bandaging was an effective way to reduce and manage oedema (as detailed in Table 1 and 2), which additionally could have beneficial effects on the healing of DFU [16, 19–26, 29, 40]. One scoping review [16] was found which explored the effect of compression bandaging on the healing of DFU.…”
Section: Resultsmentioning
confidence: 99%
“…This scoping review found eleven pieces of information across all of the literature, suggesting that compression bandaging was an effective way to reduce and manage oedema (as detailed in Table 1 and 2), which additionally could have beneficial effects on the healing of DFU [16, 19–26, 29, 40]. One scoping review [16] was found which explored the effect of compression bandaging on the healing of DFU. Compression bandaging was deemed to be safe in those without severe arterial compromise.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations